2016
DOI: 10.1089/jamp.2015.1265
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery Using Jet Nebulizer and Vibrating Mesh Nebulizer During High Frequency Oscillatory Ventilation: An In Vitro Comparison

Abstract: During HFOV, aerosol delivery with the nebulizer placed at proximal was greater than placement distal from the ETT, with VMN delivering more drug than JN. The inhaled drug was delivery correlated positively with ETT size, MAP, and bias flow, and inversely proportional to power settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Our data also confirms similar findings with DiBlasi et al (27) who observed greater nebulized iloprost delivery in the proximal than distal position for their neonatal model. Generally as model size increases drug delivery tends to increase as well in in-vitro studies due to the advantages of increased tidal volumes, and larger bore circuitry (15, 23). We speculate that the larger observed differences in drug delivery in the distal position with adult testing may be best explained by the reservoir-like effect of the aerosol gathering in the inspiratory limb during exhalation which may result in a larger bolus of drug delivered to the lungs than when the nebulizer is placed proximally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also confirms similar findings with DiBlasi et al (27) who observed greater nebulized iloprost delivery in the proximal than distal position for their neonatal model. Generally as model size increases drug delivery tends to increase as well in in-vitro studies due to the advantages of increased tidal volumes, and larger bore circuitry (15, 23). We speculate that the larger observed differences in drug delivery in the distal position with adult testing may be best explained by the reservoir-like effect of the aerosol gathering in the inspiratory limb during exhalation which may result in a larger bolus of drug delivered to the lungs than when the nebulizer is placed proximally.…”
Section: Discussionmentioning
confidence: 99%
“…During HFOV, nebulizer placement in the Distal Position has been shown to deliver negligible medication (15) thus only delivery in the Proximal Position was tested (nebulizer placed between patient wye connector and ETT) (Figure 1B). …”
Section: Methodsmentioning
confidence: 99%
“…MV is used for the most seriously ill and critical patients, but more recently there has been a general trend towards less invasive means of ventilatory support for many such patients. [54][55][56] 52,[60][61][62][63] These investigations generally showed that aerosol devices are more efficient when placed at the ventilator or humidifier and less efficient at or near the Y-piece when bias flow was present ( Figure 1). 61 Berlinski and Willis showed that a VMN delivers ninefold more aerosol dose compared with a JN during simulated mechanical ventilation.…”
Section: The Vibrating Mesh Nebulisermentioning
confidence: 99%
“…Several in vitro studies demonstrated decreased delivered drug doses from nebulisers when humidification was placed within the circuit , as well as in vivo evidence of the same effect in adults inhaling nebulised antibiotics . Moreover, placement of aerosol‐generating devices proximal to the humidifier within the circuit results in very limited drug delivery in in vitro models . Despite the known effect of humidification on nebuliser effectiveness, the risk of damaging the patients airway by inhaling dry air and disconnecting the ventilator circuit means that it may be more appropriate to increase the period of treatment with a nebuliser, rather than discontinuing humidification .…”
Section: Impact Of Respiratory Support Equipment On Drug Deliverymentioning
confidence: 99%